Effect of Leverage, Liquidity, Accounts Receivable Turnover, Inventory Turnover, and Working Capital Turnover on Return on Investment in Food and Beverage Companies Listed on the Indonesia Stock Exchange for the Period 2018-2020 - Siti Dini; Erikah Erikah; Sany Sany (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this test and analysis is to determine effect of leverage, liquidity, accounts receivable turnover, inventory turnover, and working capital turnover on return on investment in Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2018-2020. This type of research is quantitative research. The population in this study is the Food and Beverage Companies Listed on the Indonesia Stock Exchange as many as 27 issuers. The criteria that are known to be obtained are 36 of the 12 issuers for 5 years, namely the 2018-2020 period. The analytical method used is multiple regression analysis. Which consists of a partial test (t) and simultaneous test (F). The results show that leverage has a negative and insignificant effect on return on investment. Liquidity has a positive and insignificant effect on return on investment. Accounts receivable turnover has a positive and insignificant effect on return on investment. Inventory turnover has a negative and insignificant effect on return on investment. Working capital turnover has a negative and insignificant effect on return on investment. Leverage, liquidity, accounts receivable turnover, inventory turnover, and working capital turnover have a significant effect simultaneously on return on investment.